A new probably autosomal recessive cardiomelic dysplasia with mesoaxial hexadactyly. Issue 2 (April 1981) - Martínez, R Martínez Y; Corona-Rivera, E; Jiménez-Martínez, M; Ocampo-Campos, R; García-Maravilla, S; Cantú, J M
Abstract : A distinct probably autosomal recessive syndrome was ascertained in a 17-year-old boy and his deceased sister. The main features were cardiac dysplasia, peculiar facies, central bilateral (mesoaxial) hexadactyly, synmetacarpalia, short stature, ocular torticollis, and delayed puberty.